Pengaruh Ketebalan Coran Dan Temperatur Tuang Terhadap Sifat Fluiditas Aluminium Kaleng Bekas Dengan Metode Pengecoran Lost Foam Casting - Sangaji, Dediyanto A; Tjiroso, Bambang; Karim, Ivan Junaidy Abd (Patria Artha Technological Journal, 2024)
This study aims to determine the effect of casting thickness and pouring temperature on the fluidity properties of used aluminum cans. In addition, this study was also conducted to determine the defects that occur in used aluminum can castings. The casting method used in this research is the lost foam casting method with variations in pouring temperatures of 670°C, 700°C and 730°C. and variations in the thickness of the castings, namely 2 mm, 4 mm, 6 mm and 8 mm to determine the fluidity value of used aluminum cans. Observations made are defects that occur in the castings. The results showed that in the thickness of the mold pattern with a temperature of 670°C, 700°C and 730°C fluidity increases with increasing pouring temperature. At a temperature of 670°C, the fluidity length is 38 mm, at a temperature of 700°C the fluidity length is 48 mm and at a temperature of 730°C the fluidity value increases to 113 mm. However, in addition to increasing the fluidity value, there are several casting defects that occur in the castings, namely, the occurrence of external shrinkage at 670°C, air cavities at 700°C, and pinhole defects at 730°C.